PKM Ecommerce, Packaging Design dan Manajemen Pemasaran untuk Usaha Kuliner Kota Batam - Muhammat Rasid Ridho; Pastima Simanjuntak; Desrini Ningsih (Universitas Serang Raya, 2019)
Culinary business is very developed in Batam City. Moreover, the majority of people are workers. Because they do not have time to cook, people prefer to buy food outside while relaxing with family. More and more demand, more and more businesses have also opened up in this culinary field. So that competition in selling gets heavier. This service activity aims to increase the market share of Miss Tape and Toteles Donuts through the use of e-commerce, design improvement, and marketing management fostering. The result of the service that has done is the creation of partner websites to promote their products, attractive design packaging (packaging design) becomes its concern for buyers. Taste does determine the repurchase, with a beautiful look that is expected to add positive value to the customer's eyes. Dedicated solutions will require implementation by creating unique shapes and different print layouts. Marketing management is doing by guiding how businesses can maintain business continuity and still pay attention to buyer satisfaction. More details are: analyzing, planning, implementing, and monitoring the program so that the goals of culinary business continue to advance and develop.